1998
DOI: 10.1038/sj.bjp.0701851
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ro 04‐6790 and Ro 63‐0563: potent and selective antagonists at human and rat 5‐HT6 receptors

Abstract: 1 This study describes the in vitro characterization of two potent and selective 5-HT 6 receptor antagonists at the rat and human recombinant 5-HT 6 receptor. 2 In binding assays with [ 3 H]-LSD, 4-amino-N-(2,6 bis-methylamino-pyrimidin-4-yl)-benzene sulphonamide (Ro 04-6790) and 4-amino-N-(2,6 bis-methylamino-pyridin-4-yl)-benzene sulphonamide (Ro 63-0563) had mean pK i values +s.e.mean at the rat 5-HT 6 receptor of 7.35+0.04 and 7.83+0.01, respectively and pK i values at the human 5-HT 6 receptor of 7.26+0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(109 citation statements)
references
References 16 publications
2
107
0
Order By: Relevance
“…Some studies indicated that 5-HT 6 R antisense oligonucleotides (Bourson et al, 1995;Sleight et al, 1996) or 5-HT 6 R antagonists (Unsworth and Molinoff, 1994;Sleight et al, 1998;Bentley et al, 1999;Routledge et al, 1999) produced yawning-stretching behaviors that could be blocked by the muscarinic cholinergic antagonist atropine or potentiated by the cholinesterase inhibitor physostigmine. Other studies have implicated Rs in the modulation of cognitive processes (Russell and Dias, 2002).…”
Section: -Ht 6 R-influenced Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies indicated that 5-HT 6 R antisense oligonucleotides (Bourson et al, 1995;Sleight et al, 1996) or 5-HT 6 R antagonists (Unsworth and Molinoff, 1994;Sleight et al, 1998;Bentley et al, 1999;Routledge et al, 1999) produced yawning-stretching behaviors that could be blocked by the muscarinic cholinergic antagonist atropine or potentiated by the cholinesterase inhibitor physostigmine. Other studies have implicated Rs in the modulation of cognitive processes (Russell and Dias, 2002).…”
Section: -Ht 6 R-influenced Behaviorsmentioning
confidence: 99%
“…Thus, the expression pattern and pharmacological properties of Rs indicate that they may contribute to serotonergic modulation of clinically relevant neuropsychological processes and psychopharmacological responses. Administration of 5-HT 6 R antagonists and antisense oligonucleotides have been reported to produce several behavioral effects in rodents, including feeding suppression (Svartengren et al, 2004), yawning and stretching (Bourson et al, 1995;Sleight et al, 1996;Sleight et al, 1998;Bentley et al, 1999), decreased anxiety-related behaviors (Hamon et al, 1999), and improved performance in learning and memory tasks (Meneses, 2001;Rogers and Hagan, 2001;Woolley et al, 2001;Russell and Dias, 2002;Lindner et al, 2003;Riemer et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Only three mammalian 5-HT receptors are known to be positively coupled to adenylyl cyclase (5-HT 4 , 5-ht 6 and 5-HT 7 ). Under the current assay conditions neither the 5-HT 4 nor 5-ht 6 selective antagonists (RS36904 and Ro 04-6790, respectively (Hegde et al, 1995;Sleight et al, 1998)) prevented 5-HT-induced increase in adenylyl cyclase stimulation, making it unlikely that either of these receptors contribute to the resultant elevation in cyclic AMP. Because no selective 5-HT 7 receptor antagonist was available to us, we examined the e ects of non-selective 5-HT antagonists which have high a nity, and some selectivity, for the 5-HT 7 over either 5-HT 4 or 5-ht 6 receptors.…”
Section: 7-dht-induced Changes In Hypothalamic Pindolol-insensitivementioning
confidence: 97%
“…This response was too small to permit a full dose-response analysis (being only 110+2% above basal with 1 mM 5-HT) but was evident in every experiment permitting pharmacological characterization of the stimulation with a single concentration of 5-HT ( Figure 5). The 5-HT-induced stimulation of adenylyl cyclase was not prevented by incubation with either the selective 5-HT 4 antagonist, 1-(4-amino-5-chloro-2-(3,5-dimethoxy)benzyloxyphenyl)-3-[1-((2-methylsulphonylamino)ethyl)-piperidin-4-yl]1-propanone (RS36904, 100 nM, (Hegde et al, 1995)) or the 5-ht 6 antagonist, 4-amino-N-(2,6 bis-methylamino-pyrimidin-4-yl)-benzene sulphonamide (Ro 04-6790, 1 mM, (Sleight et al, 1998)) at concentrations approximately ten times their respective pA 2 values determined in rat tissues. In contrast, the 5-HT-induced stimulation was signi®cantly attenuated by the presence of either mesulergine (250 nM), ritanserin (450 nM) or methiothepin (200 nM) all of which have high a nity, and some selectivity, for the 5-HT 7 compared with either the 5-HT 4 or 5-ht 6 receptor (Bard et al, 1993).…”
Section: -Ht-induced Adenylyl Cyclase In Hypothalamic Membranesmentioning
confidence: 99%
“…Nine other 5-HT antagonists had no antagonist activity up to 10 74 M. These antagonists included compounds speci®c for the 5-HT 3 (metoclopramide, MDL72222) or 5-HT 3 and 5HT 4 subtype (tropisetron, Dumuis et al, 1988), the 5-HT 6 subtype (Ro 04-6790, Ro 63-0563, Sleight et al, 1998;olanzepine, Roth et al, 1994), the 5-HT 4 subtype (GR113808, Gale et al, 1994), the 5-HT 2A (ketanserin) and 5-HT 1A/B (pindolol) subtypes. This data suggested that 5-HT-induced pigment dispersion in melanophores is mediated by an endogenous 5-HT 7 receptor subtype.…”
Section: High Concentrations Of Melatonin Activate Pigment Dispersionmentioning
confidence: 99%